Natural killer lytic-associated molecule plays a role in controlling tumor dissemination and metastasis - Hoover, Richard G.; Gullickson, Gail; Kornbluth, Jacki (Frontiers in Immunology, 2012)
Natural killer lytic-associated molecule (NKLAM) is an E3 ubiquitin ligase that plays a major role in the cytolytic activity of NK cells. NKLAM is rapidly synthesized and then targeted to the granule membranes of NK cells upon NK activation. Previous studies have shown an essential role for NKLAM in NK killing activity in vitro. These findings were extended to an in vivo model of NK-mediated tumor killing in which NKLAM-deficient knockout (KO) mice injected with B16 melanoma cells were found to have significantly higher numbers of pulmonary tumor nodules than wild type (WT) mice. To further investigate the role of NKLAM and NK function in tumor immunity in vivo, we utilized additional tumor models to compare tumor development and progression in NKLAM KO and WT mice. Primary tumor growth, dissemination, and metastasis of RMA-S lymphoma cells and E0771 breast cancer cells were evaluated. Both tumor cell lines were stably transfected with constructs that allow expression of green fluorescent protein (GFP), which serves as a tumor-specific marker. Intravenous injection of NK-sensitive RMA-S lymphoma cells resulted in greater dissemination of lymphoma cells in NKLAM KO mice than in WT mice. Lymphoma cells were found in the lymph nodes and bone marrow of NKLAM KO mice two weeks after injection; few detectable tumor cells remained in WT mice. E0771 syngeneic breast cancer cells were injected into the mammary pads of NKLAM KO and WT mice. Primary tumor growth was greater in NKLAM KO than in WT mice. More significantly, there were four to five fold more tumor cells in the blood and lungs of NKLAM KO than in WT mice two weeks after injection of tumor cells into the mammary pad. These results indicate that NKLAM plays a role in tumor development in vivo, especially in controlling tumor dissemination and metastasis to distant sites.